Шугаман шингээлттэй, шугаман бус суурь дахь эллипс туйлшралтай долгион - Д, Улам-Оргих; Г, Очирбат; О, Нямсүрэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
The scheme used in asymptotical methods of Krilov-Bogolubov-Metropolsky modified to solve full set of Maxwell equation in propagation problem of stationary optical waves in nonlinear Kerr like substrate with linear absorption. Asymptotical series obtained with the help of such scheme affords one to get reflection regime of elliptically polarized light waves from the absorbing substrate surface.